Effects of nitrogen deposition and liming on the early regeneration of two dominant tree species in a subtropical forest of China. Issue 3 (3rd July 2019) - Han, Wenjuan; Jiang, Jia; He, Qinru; Huang, Huifang; Hu, Jiahong; Hu, Shimeng; Ni, Jian
ABSTRACT: To assess the effects of nitrogen deposition and liming on the early regeneration of two dominant tree species, Pinus massoniana and Schima superba, in a subtropical forest of China, we conducted a greenhouse experiment at three nitrogen deposition levels (0, 10, and 20 g N m −2 year −1 ) and two liming levels (0 and 100 g CaCO3 m −2 year −1 ). Results showed that (1) nitrogen deposition decreased the seed germination and seedling survival of P. massoniana, but did not affect those of S. superba ; (2) high nitrogen deposition decreased the height and diameter of P. massoniana, but did not affect the diameter of S. superba, and low nitrogen deposition increased the height of S. superba ; (3) high nitrogen deposition decreased the aboveground, belowground, and total biomass of P. massoniana and only reduced the aboveground biomass of S. superba ; (4) liming increased the height of S. superba under a high nitrogen deposition, but decreased the height of P. massoniana regardless of nitrogen deposition levels. These results indicate that increased nitrogen deposition may render the habitat suitable for S. superba growth, but reduce the P. massoniana population. Liming appears ineffective in mitigating the negative effects of high nitrogen deposition in this region.